The availability of health information to patients with newly diagnosed polymyalgia rheumatica: results from the Polymyalgia Rheumatica (PMR) Cohort study - Tshimologo, Maatla (Prim Health Care Res Dev, 2018)
AIM: The aim of this study was to assess the provision of information to, and seeking of information by, patients newly diagnosed with polymyalgia rheumatica (PMR) in primary care. BACKGROUND: PMR is an inflammatory rheumatological condition of older people that can be treated with long-term oral glucocorticoids. Management usually requires the patient to understand the potential complications of treatment and the disease, as well as involvement in reducing treatment dose. This may be complex for patients to understand. METHOD: Data are taken from the baseline phase of the PMR Cohort study, which recruited newly diagnosed patients with PMR from UK primary care. Participants provided information on their PMR symptoms, general health and sociodemographics. They also completed items regarding information provision by their doctor at diagnosis, its usefulness and their own search for information. FINDINGS: A total of 652 people responded to the baseline survey. In all, 399 (62.7%) had received written information from their doctor; 237 (98%) found it useful; 265 (42.9%) would have liked more information; and 311 (48.4%) sought out more information. Those who were not given information and did not seek it out tended to be older and have poorer internet access. Information provided at diagnosis to patients with PMR is useful, but more than a third did not receive any. This is concerning when PMR requires self-management and vigilance for red flags. Doctors should make use of the resources already available to them to support patients and should specifically ensure that these are available to more elderly patients and those without internet access.